Effects of Imidacloprid-Contaminated Feed Exposure on Hematological Parameters in Adult Rabbits (Oryctolagus Cuniculus) (Research in Agriculture Livestock and Fisheries, 2020)
Blood parameters are an important index to assess the body homeostasis in mammals. Here, the effect of pesticide (imidacloprid) contaminated feed exposure on the haematological parameters of adult rabbits (n=15) was studied. Pesticides (Imidacloprid, Bildor® 0.5ml (100mg)/L water spray on vegetables and green grass) exposed feed fed to rabbits with wash (washed feed rabbit) or without a wash (not washed feed rabbit) in the once-daily morning for every alternative day up to 15 days. Control rabbits have received a standard diet (fresh vegetables and green grass). The blood cell analysis showed that the total erythrocyte count, packed cell volume, and haemoglobin values were not changed significantly in pesticide exposed rabbit. For differential leukocyte count, the percentage of neutrophil and eosinophil was significantly decreased in the pesticide-exposed rabbit as compared to the control rabbit. The lymphocyte percentage was increased significantly in pesticide-exposed rabbits compared to control rabbits. Interestingly, the number of lymphocytes was significantly increased in not washed feed rabbits compared to wash feed rabbits. The results of the present study suggest that residue of agriculturally used pesticides may affect the body homeostasis of animals.Res. Agric., Livest. Fish.7(3): 439-444,  December 2020